Determining the knee joint laxity between the pronated foot and normal arched foot in adult participants: Knee joint laxity between pronated and normal arched foot - Alahmri, Fayez; Alsaadi, Saad; Ahsan, Mohammad; Alqhtani, Sarah (Acta Biomedica Atenei Parmensis, 2022)
Aim of the Study: Foot pronation is often associated with increased internal rotation of the lower limb, predisposing the knee joint to greater stress. However, the impact of the pronated foot on knee joint laxity has not been well understood. The study aims to find out the effect of the pronated foot on knee joint laxity.Methods: Forty adult participants were recruited for the study: 20 with asymptomatic pronated foot and 20 control subjects with the normal arched foot. Foot assessments were performed by navicular drop test and rearfoot angle measurements. Knee joint laxity was measured by a KT 1000 arthrometer of the dominant leg. An independent t-test was performed to detect the differences between both groups.Results: Both groups were similar in age, BMI and physical activity level. The findings showed no significant differences between the pronated foot and control group in the knee joint laxity (P = 0.645).Conclusions: There were no significant differences in anterior knee displacement between the pronated foot and normal arch foot. The study showed that pronated foot might not be responsible for ACL injuries during the age of twenties and cofounding factors. Further research is needed to investigate older subjects with the pronated foot.